PECULIARITIES OF MEDIEVAL HOUSEBUILDING ON THE TERRITORY OF PERM KRAI - Krylasova, N.B. (Perm Federal Research Centre Journal, 2017)
On the basis of the new sources, received during PSHPU Kama archaeological ethnographical expedition excavations (KAEE), the analysis of structural peculiarities of medieval dwellings was carried out at 2 ancient settlements and 2 village settlements belonging to the Lomovatovskaya and Rodanovskaya archaeological cultures (18 dwellings). All dwellings were large, mainly of a frame-long-pillar construction, had a gable overlap with a framework on long-pillar supports. The central place of the interior belonged to furnace and hearth remains and storage-pits located along the axial line. A plank bed was situated along the perimeter with a width of 2 m on the average, under which storage-pits were also placed; the floors were plank with joists, sometimes covered with clay. The presence of trenches along the perimeter of dwellings, obviously connected with the construction of mounds of earth, is typical for the Lomovatovskaya cultural period (till the end of the 11th century). Trenches disappeared in the Rodanovskaya cultural period, the interior of dwellings became more complicated, partitions, separating those dwellings into two rooms, as well as various constructions that can be associated with table supports and other interior items appeared. There are reasons to assume the presence of two-story dwellings at Rozhdestvenskoye ancient settlement.